The Relationship Between Tauke and Farmers in the Rice Farming System in Seberang Village, Riau Province - Husniah, Wildatul; Yusuf, Yusmar; Rosaliza, Mita (Journal of Authentic Research, 2026)
The relationship between Tauke and farmers in rural areas is not merely economically exploitative. In practice, Tauke also plays a positive role in supporting farming activities, particularly by improving production time efficiency through the adoption of modern technology. This study aims to analyze the Tauke’s contribution to supporting time efficiency in rice farming in Seberang Village through the adoption of modern technology. This is a qualitative study using a case study method; data were collected through observation, in-depth interviews with seven informants, and a literature review. The Tauke's technological modernization manifests in the provision of rice harvesters. This equipment has a positive impact in the form of harvest time efficiency for farmers. On the other hand, this technological support is also a strategy by the tauke to increase productivity, as the use of machines allows for more optimal harvest yields. However, this support can simultaneously be interpreted as an effort to maintain farmers’ dependence, as it may limit their ability to operate independently without the technological assistance provided by the tauke, which could hinder their long-term self-sufficiency and decision-making in agricultural practices. This study confirms that the relationship between tauke and farmers should not always be assumed to be negative. In certain contexts, such as those found in this study, Tauke makes positive contributions and supports farmers’ work efficiency by providing resources, knowledge, and access to markets that enhance productivity and sustainability. Implicitly, this study recommends that tauke could serve as partners for the government in local economic development, particularly in areas far from urban centers or with limited access to public amenities.